الوصل السببي في سورة مريم وأثرهما في التماسك النصي - برير زينب; حريزي وجدان (University of El-Oued جامعة الوادي, 2025)
يهدف البحث إلى دراسة الوصل السببي والسببية في سورة مريم وأثرهما في التماسك النصي. مما أدى فيه إلى التعرف على لسانيات النص والمعايير النصية التي اهتمت بها وكذا آليات التصاق النصي. كما اعتمدنا على الوقوف في النص القرآني على سورة مريم برواية ورش، والوقوف على أثر الوصل السببي والسببية في التماسك النص This research aims to study causal connection and causality in Surah Maryam and their impact on textual cohesion. This led to an understanding of textual linguistics, the textual criteria it addresses, and the mechanisms of textual cohesion. We also examined the Qur'anic text of Surah Maryam in the Warsh narration, examining the impact of causal connection and causality on textual cohesion.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: لسانيات النص، الوصل السببي، السببية، سورة مريم; Textual linguistics; causal connection; causality; Surah Maryam